The linguistic contribution in Lévi-Strauss' "Sad Tropics - Alonzo Sutta, Alicia (2004)
The outstanding scholar of the indigenous cultures of the Amazon, Claude Lévi-Strauss carried out his field research in the Brazilian Amazon around the thirties in the last century. The expedition in which he embarks, departs from Marseille (France) aboard the ship "Capitaine Paul-Lemerle" which, starting from the Mediterranean, following the small islands of the Caribbean, will take him to Sao Paulo (Brazil). Lévi-Strauss' penchant for socio-cultural facts led him to the Matto Grosso area in southwestern Brazil.